Chronic lithium administration in a mouse model for Krabbe disease. Issue 1 (12th November 2021) - Del Grosso, Ambra; Parlanti, Gabriele; Angella, Lucia; Giordano, Nadia; Tonazzini, Ilaria; Ottalagana, Elisa; Carpi, Sara; Pellegrino, Roberto Maria; Alabed, Husam B. R.; Emiliani, Carla; Caleo, Matteo; Cecchini, Marco
Abstract: Krabbe disease (KD; or globoid cell leukodystrophy) is an autosomal recessive lysosomal storage disorder caused by deficiency of the galactosylceramidase (GALC) enzyme. No cure is currently available for KD. Clinical applied treatments are supportive only. Recently, we demonstrated that two differently acting autophagy inducers (lithium and rapamycin) can improve some KD hallmarks in‐vitro, laying the foundation for their in‐vivo pre‐clinical testing. Here, we test lithium carbonate in‐vivo, in the spontaneous mouse model for KD, the Twitcher (TWI) mouse. The drug is administered ad libitum via drinking water (600 mg/L) starting from post natal day 20. We longitudinally monitor the mouse motor performance through the grip strength, the hanging wire and the rotarod tests, and a set of biochemical parameters related to the KD pathogenesis [i.e., GALC enzymatic activity, psychosine (PSY) accumulation and astrogliosis]. Additionally, we investigate the expression of some crucial markers related to the two pathways that could be altered by lithium: the autophagy and the β‐catenin‐dependent pathways. Results demonstrate that lithium has not a significant rescue effect on the TWI phenotype, although it can slightly and transiently improves muscle strength. We also show that lithium, with this administration protocol, is unable to stimulate autophagy in the TWI mice central nervous system, whereas results suggest that it can restore the β‐catenin activation status in the TWI sciatic nerve. Overall, these data provide intriguing inputs for further evaluations of lithium treatment in TWI mice.